Pemanfaatan Limbah Jagung sebagai Peningkatan Nilai Ekonomi Bagi Masyarakat di Desa Blimbing, Kecamatan Tarokan, Kabupaten Kediri - Adam Rahmadi; Budi Heryanto; Ferdy Yunanto Yunanto; Mukti Prasaja Mukti (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The potential of corn land in the Kediri region reaches 54,650 ha/year making corn production in Kediri abundant. Seeing the potential of large land areas shows the yield of bar and needs utilization from corn waste. The production of corn can be developed into animal feed. One of them is waste or waste from corn that has been milled. Jenjet as one of the alternatives to food, especially for cattle feed. Community service in Blimbing Village, Tarokan Subdistrict, Kediri Regency in general in the management of corn milling waste is still not fully utilized. Most of the population who own farmland and cattle still rarely use jenjet for alternative cattle feed. Therefore, it is expected that the material delivered about the utilization of corn milling waste can be an education and learning for the community that in corn crops waste other than leaves and stems can also be used for animal feed.